Reforms and Updates in Culture and Art Education – Guarantee of Quality Education - Shoyuldoshova, Billura; Ahmedov, Bakhodir (International Journal on Integrated Education, 2023)
This article contains thoughts and opinions about the rapid reforms and prospective tasks in the improvement of the quality of higher education in New Uzbekistan. In particular, the activities of higher education institutions in the field of culture and art were analyzed. In this field, attention is paid to newly established higher education institutions and fundamental changes in education are discussed.